2019
DOI: 10.5897/jmpr2019.6741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aphrodisiac properties of the aqueous extract of the trunk barks of Spathodea campanulata P. Beauv. (Bignoniaceae) on albino rats (Rattus norvegicus)

Abstract: Spathodea campanulata P. Beauvois (Bignoniaceae) is a tree from the tropical and subtropical forests of Africa, used in folk medicine for the treatment of several diseases such as gastric pain, rheumatism, lumbago, cataracts and some intestinal parasites. In West Cameroon, traditional healers use a decoction of the bark of the trunk as an aphrodisiac in males. The objective of the present study was to evaluate the aphrodisiac activity of the aqueous extract of the trunk barks of S. campanulata in male rats. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, there was an increase in the weight of certain androgen-dependent organs: the prostate (7.70%), the testes (11.20%), and penis (31.81%). These results validated the androgenic potential of S. campanulata and backing the use of S. campanulata trunk bark in the treatment of erectile dysfunction (Talla et al, 2021).…”
Section: Aphrodisiac Activitysupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, there was an increase in the weight of certain androgen-dependent organs: the prostate (7.70%), the testes (11.20%), and penis (31.81%). These results validated the androgenic potential of S. campanulata and backing the use of S. campanulata trunk bark in the treatment of erectile dysfunction (Talla et al, 2021).…”
Section: Aphrodisiac Activitysupporting
confidence: 72%
“…It also reduced glycemia (29%) in alloxan-induced diabetes mellitus rats with the 400 mg/kg dose in the acute phase. The multiple dose treatment with the extract led to the decrease in alloxan-induced hyperglycemia at the end of the 18th day (Tanayen et al, 2014). The methanolic extracts of the flowering branch and bark were screened for their antidiabetic activity in mice at a dose of 500 mg/kg bw.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…The study of medicinal plants as potential agents for regulating androgen release and improving male health is therefore highly important. Indeed, several plants such as Spathodea Campanulata and Ficus asperifolia are used for their androgenic properties [4,6]. However, despite their multiple benefits, previous studies have reported that plants are the cause of 3-5% of reported poisonings in previous studies, 17% of which were associated with fatal events [7].…”
Section: Introductionmentioning
confidence: 99%